2009
DOI: 10.1038/clpt.2009.92
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Genetic Polymorphisms in the Organic Cation Transporters OCT1, OCT2, and OCT3 on the Renal Clearance of Metformin

Abstract: Organic cation transporters (OCTs) can mediate metformin transmembrane transport. We explored metformin pharmacokinetics in relation to genetic variations in OCT1, OCT2, OCT3, OCTN1, and MATE1 in 103 healthy male Caucasians. Renal clearance varied 3.8-fold and was significantly dependent on creatinine clearance (r(2) = 0.42, P < 0.0001), age (r(2) = 0.09, P = 0.002), and OCT1 polymorphisms. Carriers of zero, one, and two low-activity OCT1 alleles (Arg61Cys, Gly401Ser, 420del, or Gly465Arg) had mean renal clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
247
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(269 citation statements)
references
References 47 publications
19
247
2
1
Order By: Relevance
“…The role of single nucleotide polymorphisms (SNPs) in the interindividual response to metformin is not yet fully elucidated, but several studies suggest that polymorphisms in OCT1 alter the response to metformin treatment [25][26][27]. The current research regarding the SNP rs316019 (808 G>T) in the gene encoding OCT2 is conflicting, but it does appear to affect the renal clearance (CLR) of metformin [28,29].…”
Section: Study Participantsmentioning
confidence: 99%
“…The role of single nucleotide polymorphisms (SNPs) in the interindividual response to metformin is not yet fully elucidated, but several studies suggest that polymorphisms in OCT1 alter the response to metformin treatment [25][26][27]. The current research regarding the SNP rs316019 (808 G>T) in the gene encoding OCT2 is conflicting, but it does appear to affect the renal clearance (CLR) of metformin [28,29].…”
Section: Study Participantsmentioning
confidence: 99%
“…11,29 On the other hand, low-function SLC22A1 variants including R61C, G401S and G465R have been associated with significantly higher rates of renal clearance of metformin. 30 In addition to the effect on metformin pharmacokinetics, low-function SLC22A1 variants have been also associated with significantly decreased glucose-lowering response of metformin. 2 For the SLC22A6 gene, one haplotype block ranging from rs4149170 to rs4149172 was obtained in Asian populations, and none was defined in African-American and European-American cohorts (Figures 1 and 2d).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no report on contribution of different SNPs of OCT1 on clinical outcomes/adverse effects of morphine. Four loss of function OCT1 variants have been reported before: Arg61Cys (rs12208357), Cys88Arg (rs55918055), Gly401Ser (rs34130495) and Gly465Arg (rs34059508), and change of Met420 (rs72552763) amino acids [20,21]. Tzvetkov et al [19] showed in vitro studies that morphine uptake was increased up to fourfold in HEK293 cells overexpressing human OCT1.…”
Section: Discussionmentioning
confidence: 99%